2016
DOI: 10.1016/j.jspi.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to multiple testing of grouped hypotheses

Abstract: A twofold loop testing algorithm (TLTA) is proposed for testing grouped hypotheses controlling false discoveries. It is constructed by decomposing a posterior measure of false discoveries across all hypotheses into within-and between-group components, allowing a portion of the overall FDR level to be used to maintain control over within-group false discoveries. Numerical calculations performed under certain model assumption for the hidden states of the within-group hypotheses show its superior performance over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…The problem of multiple testing with groups and related problems have received substantial attention in the literature (Efron, ; Ferkingstad et al ., ; Cai and Sun, ; Hu et al ., ; Liu et al ., ; Barber and Ramdas, ). It can be shown that, under model (4.2), the oracle statistic (4.1) is reduced to the conditional local false discovery rate CLfdr (Cai and Sun, ) CLfdri=(1π1k)f10k(ti)/f1k(ti) for S i = k , k =1,…, K .…”
Section: Extensions and Connections With Existing Workmentioning
confidence: 97%
See 1 more Smart Citation
“…The problem of multiple testing with groups and related problems have received substantial attention in the literature (Efron, ; Ferkingstad et al ., ; Cai and Sun, ; Hu et al ., ; Liu et al ., ; Barber and Ramdas, ). It can be shown that, under model (4.2), the oracle statistic (4.1) is reduced to the conditional local false discovery rate CLfdr (Cai and Sun, ) CLfdri=(1π1k)f10k(ti)/f1k(ti) for S i = k , k =1,…, K .…”
Section: Extensions and Connections With Existing Workmentioning
confidence: 97%
“…Important recent progress for exploiting the grouping and hierarchical structures among hypotheses under more generic settings has been made in Liu et al . (), wherein an interesting decomposition of the oracle statistic was derived:TORifalse(t,sfalse)=1false{1P(θ2i=0|t,s)false}false{1P(θ1i=0|t,s,θ2i=1)false}.The decomposition explicitly shows how the auxiliary statistic can be used to adjust the Lfdr‐statistic, and provides insights on how the grouping effects S i and individual effects T i interplay in simultaneous testing. The logical correlation (2.2) can be conceptualized as a hierarchical constraint and exploited more efficiently (Sarkar and Zhao, ).…”
Section: Extensions and Connections With Existing Workmentioning
confidence: 99%
“…This model will be revisited in later sections. See also Ferkingstad et al (2008), Hu et al (2010) and Liu et al (2016) for related works on multiple testing with groups.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Liu et al, (), Sarkar and Zhao () proposed a two‐stage procedure where the groups are non‐overlapping. In our approach the groups are generally overlapping and the decisions regarding different hypotheses depend upon each other.…”
Section: A New Bayesian Non‐marginal Multiple Testing Proposalmentioning
confidence: 99%
“…In Web Appendix E.2, we discuss the equivalence of forming groups on the basis of prior correlation and genomic distance between miRNAs and elaborate specifics on group formation. Liu et al (2016), Sarkar and Zhao (2017) proposed a twostage procedure where the groups are non-overlapping. In our approach the groups are generally overlapping and the decisions regarding different hypotheses depend upon each other.…”
Section: New Error Basedmentioning
confidence: 99%